The social dynamics of group offending - Weaver, Beth (Theoretical criminology, 2022)
Theoretical explanations of group offending have been hindered by a focus on rational actor models of social relationships. One consequence of this has been a neglect of the dynamics of social relations and their role in group offending and desistance. Drawing illustratively on two studies conducted in the West of Scotland, this article advances an integrated theoretical framework for the comparative study of group offending that moves beyond either individualizing or ‘gang’ frames dominating existing discourse, towards a thick understanding of situated social relations. By integrating Bourdieu’s concept of habitus with Donati’s relational realist framework, this article theoretically and empirically examines the dynamics of group offending relationships, what shapes them and the way they can, in turn, shape and affect offending and desistance trajectories.